Self-assessment of an organisation according to the Polish Quality Award model on the example of an automotive company – self-assessment process, selected improvement actions - Szewczyk, Karol (Samoocena organizacji według modelu PNJ na przykładzie przedsiębiorstwa branży motoryzacyjnej – proces samooceny, wybrane działania doskonalące, 2019)
The purpose of this paper is to describe the characteristics of organizational self-assessment and its practical use in everyday life. The material presented discusses the process of performance measurement based on examples from the automotive industry. Focus was placed on the model requirements of the Polish Quality Award (PNJ), after the assessment results present the values in each area of the criteria, their potentials for improvement and examples of corrective actions are indicated . The examples contain solutions in the area of communication improvements and employee suggestion programs.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 48-57
Keywords: company self-assessment; continous improvement; Polish Quality Award; PNJ; samoocena organizacji; ciągłe doskonalenie; model Polskiej Nagrody Jakości